2021
DOI: 10.3389/fonc.2021.658543
|View full text |Cite
|
Sign up to set email alerts
|

Using Liposomes to Alleviate the Toxicity of Chelerythrine, a Natural PKC Inhibitor, in Treating Non-Small Cell Lung Cancer

Abstract: Aim of the StudyCHE can inhibit the proliferation of lung cancer cells and induce apoptosis. However, despite having in vivo toxicity, CHE has not been thoroughly investigated in term of its in vivo antitumor effect. The present study evaluated the antitumor effect of CHE on non-small cell lung cancer cell line HCC827.MethodsThe antitumor effect of CHE on HCC827 was evaluated, and its potential work mechanism was investigated. CHE long circulation liposomes (CHELPs) modified with polyethylene glycol have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Moreover, the main mechanism of action is correlated with the alteration of phosphoinositide 3-kinase (PI3K), Akt, and the mammalian target of rapamycin (mTOR) signaling pathways [ 35 ]. Chelerythrine ( 2 ) has exhibited anticancer activity in vivo and in vitro, and considerable existing research has confirmed that chelerythrine can act on different pathways (e.g., DNA, MAPK, apoptosis, ROS, cell cycle, autophagy, tumor metastasis, and PKC) to inhibit or facilitate apoptosis in a variety of cancer cells (e.g., non-small cell lung cancer [ 36 ], prostate cancer [ 37 ], lung adenocarcinoma [ 38 ], renal cancer [ 39 ], and melanoma cells [ 40 ], colorectal cancer [ 41 ]), thus suggesting that the benzophenanthridine alkaloids exhibit high anticancer activity. Previous studies have proven that chelerythrine ( 2 ) exhibits antitumor stem cell properties, which are mediated by the downregulation of β- Catenin expression, thus inhibiting non-small cell lung cancer stem cells [ 42 ].…”
Section: Antitumor Activities Of Benzophenanthridine Alkaloids From N...mentioning
confidence: 99%
“…Moreover, the main mechanism of action is correlated with the alteration of phosphoinositide 3-kinase (PI3K), Akt, and the mammalian target of rapamycin (mTOR) signaling pathways [ 35 ]. Chelerythrine ( 2 ) has exhibited anticancer activity in vivo and in vitro, and considerable existing research has confirmed that chelerythrine can act on different pathways (e.g., DNA, MAPK, apoptosis, ROS, cell cycle, autophagy, tumor metastasis, and PKC) to inhibit or facilitate apoptosis in a variety of cancer cells (e.g., non-small cell lung cancer [ 36 ], prostate cancer [ 37 ], lung adenocarcinoma [ 38 ], renal cancer [ 39 ], and melanoma cells [ 40 ], colorectal cancer [ 41 ]), thus suggesting that the benzophenanthridine alkaloids exhibit high anticancer activity. Previous studies have proven that chelerythrine ( 2 ) exhibits antitumor stem cell properties, which are mediated by the downregulation of β- Catenin expression, thus inhibiting non-small cell lung cancer stem cells [ 42 ].…”
Section: Antitumor Activities Of Benzophenanthridine Alkaloids From N...mentioning
confidence: 99%
“…Another study on the NSCLC cell line (HCC827) reported the efficacy of CHE in inducing apoptosis and inhibiting cell growth by inducing ROS release and downregulating caspase-3 and PKC-ϵ expression. CHE imparted anticancer effects on HCC827 by inhibiting PKC and caspase-3 activation, which were blocked by PMA, a PKC activator, thereby proving that CHE inhibited cancer cell viability and proliferation and induced cell apoptosis through the ROS/PKC-ϵ/caspase three pathway and glycolysis ( Wang et al, 2021 ).…”
Section: Role Of Chelerythrine In a Variety Of Human Cancersmentioning
confidence: 99%
“…In addition, an in vivo study proved that CHE exerted specific anticancer effects on concentration adjustment to inhibit the Wnt/β-catenin pathway in different lung cancers and facilitate cancer cell apoptosis, inhibiting the proliferation and diminishing the self-renewal capacity of human lung cancer stem cells (HLCSCs) by downregulating β-catenin, SOX2, and MYC ( Heng and Cheah, 2020 ; Wang et al, 2021 ). Owing to the inhibition of the tumorigenic activity of HLCSCs by CHE, which can inhibit cancer growth, the CHE concentration can be flexibly adjusted to protect against different specific targets in different cancers.…”
Section: Role Of Chelerythrine In a Variety Of Human Cancersmentioning
confidence: 99%
See 2 more Smart Citations